A kockázati- és magántőke forrásai. Az intézményi befektetők szerepe a kockázati- és magántőke-ágazat forrásellátásában - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, 2010)
– Due to the 2008 global financial crisis the position of the private equity sector has weakened. The number and the value of new transactions have dropped together with the volume of the raised funds. Credit shares have also decreased in the financing of the transactions. Exiting from the portfolio companies became more difficult, which slowed down the capital reimbursement to the private equity investors. However in spite of the crisis, the attractiveness of the private equity investments remain positive among investors, since they produced better returns than public markets. While Hungary became less attractive from the standpoint of the regional private equity funds specialized in high-value buyouts, the country remained the leader in setting up Jeremie funds, and in the liberal regulation of the private pension funds until the autumn of 2010, which can boost the private equity investments. This could support the development of small- and medium-cap enterprises, suffering from shrinking resources due to the crisis. The prospected "nationalization" of private pension funds may put this process on hold.
Keywords: G23; G24; 330; venture capital; private equity; institutional investors; pension funds; Risikokapital; Private Equity; Institutioneller Investor; Pensionskasse; Ungarn